1981
DOI: 10.1159/000153197
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin Subtypes in Six Indian Population Samples

Abstract: Transferrin subtypings have been performed on three population samples originating from Himachal Pradesh, North India (Pangwala, Gaddi-Bharmour valley, Gaddi-Kangra district) and on three samples from Andhra Pradesh, South India (Koya, Konda Kammara, Lambadi). Among these six populations, marked differences in the distribution of Tf phenotype and allele frequencies are present. All Indian samples differ clearly from the hitherto reported TfC1 and TfC2 allele frequencies. In one of our Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 2 publications
3
14
0
Order By: Relevance
“…There is no other report on the distribution of TJ'C subtypes in the populations of Iran or Parsis in In dia. The gene frequencies of TfC] and Tfc2 observed in the present population of the Parsis are within the range of gene fre quencies of these alleles reported in other Indian populations [Saha and Tan, 1983;Kamboh and Kirk, 1983;Walter et al, 1981Walter et al, , 1983 and in Jordanian Arabs [Saha, 1985a], T fD was not detected in the present 253 and earlier 240 Parsis . This variant is occasionally re ported in some groups of India at a very low frequency.…”
Section: Methodssupporting
confidence: 83%
“…There is no other report on the distribution of TJ'C subtypes in the populations of Iran or Parsis in In dia. The gene frequencies of TfC] and Tfc2 observed in the present population of the Parsis are within the range of gene fre quencies of these alleles reported in other Indian populations [Saha and Tan, 1983;Kamboh and Kirk, 1983;Walter et al, 1981Walter et al, , 1983 and in Jordanian Arabs [Saha, 1985a], T fD was not detected in the present 253 and earlier 240 Parsis . This variant is occasionally re ported in some groups of India at a very low frequency.…”
Section: Methodssupporting
confidence: 83%
“…commun.]. The TFC12 allele, previously desig nated C9 and Cpangwala [Walter et al, 1981a;Yuasa et al, 1983a], has been found to be present at polymorphic fre quency in Nepalese and some Indian pop ulations and may well represent a marker of populations of the Indian subcontinent. The last TF C subtype, TF Cl3 [originally called C6: Kamboh and Kirk, 1983], has been reported to be restricted to Austral ian Aboriginal populations where it exists at polymorphic level.…”
Section: Tfc Allelesmentioning
confidence: 99%
“…Interestingly the DChi variant has also been encountered in the Veddahs of Ceylon, North East and South Indian tri bal populations in the Indian subconti nent [Rao et al, 1979;Walter et al, 1981a;Giri et al, 1985] as well as in Finland [Beckman et al, 1975], and indicates the extent of penetration of Mongoloid genes into these neighbouring populations. Its complete absence in the Pacific and Aus tralian regions and its patchy distribution in the lesser Sunda Islands of Indonesia suggests that the Mongoloid migration did not proceed beyond the South East limit of Indonesia.…”
Section: Tf B and D Allelesmentioning
confidence: 99%
“…Up to now Tf subtype allele frequencies are known for Himachal Pra desh [Walter et al, 1981a], Sikkim [Bhasin et al, in preparation], Manipur [Singh et al, 1986], West Bengal [Reddy et al, 1984], Gujarat [Walter et al, 1984], Karna taka [Kumar et al, in preparation], and Andhra Pradesh [Walter et al, 1981b], Gc subtype allele frequencies are known for Himachal Pradesh [Papiha, 1981;Papiha et al, 1983], Punjab [Papiha et al, 1982], Sikkim [Bhasin et al, in preparation], Manipur [Singh et al, 1986], Karnataka [Kumar etal., in preparation], and Andhra Pradesh [Walter et al, 1984], In order to enlarge our knowledge on the distribution of Tf and Gc subtype al leles in India we report in this paper on the frequency of these alleles in 10 different population groups of Assam ( fig. 1): Brah mins, Kalitas, Kaibartas, Rajbanshis, Muslims, Ahoms, Chutias, Kacharis, Kar bis and Sonowals.…”
Section: Introductionmentioning
confidence: 99%